Influence of Audio-Musical Activities on Literacy of Five Years Old Children - Magán-Hervás, Alexandra; Gértrudix-Barrio, Felipe (Revista Electrónica Educare, 2017)
Pre-school education period is the foundation for children development. Teachers must reinforce students’ knowledge in this stage since all the contents covered will impact throughout their lives. Due to its educational value and influence on the different aspects of children development, music should be regarded as an essential resource in these early learning stages. In this regard, this work aims to analyze if the activities including music, hearing, and sound have a positive influence on the unfolding of literacy skills on five-year-old children. To accomplish such objectives, qualitative, quantitative, and triangulation methodologies have been used by taking the content analysis from the literature review related to the topic of this investigation and then after, by using the experimental design technique (pre-test/experiment/post-test) with two design types (experimental and controlled class) from the research-action paradigm. Considering the results of this research, it can be asserted that audio-musical activities significantly influence reading and writing skills acquisition without noteworthy differences between boys and girls.